Novel Acetamide Indirectly Targets Mycobacterial Transporter MmpL3 by Proton Motive Force Disruption - Shetty, Annanya; Xu, Zhujun; Lakshmanan, Umayal; Hill, Jeffrey; Choong, Meng Ling; Chng, Shu-Sin; Yamada, Yoshiyuki; Poulsen, Anders; Dick, Thomas; Gengenbacher, Martin (Frontiers in Microbiology, 2018)
To identify novel inhibitors of Mycobacterium tuberculosis cell envelope biosynthesis, we employed a two-step approach. First, we screened the diverse synthetic small molecule 71,544-compound Enamine library for growth inhibitors using the non-pathogenic surrogate Mycobacterium bovis BCG as screening strain and turbidity as readout. Second, 16 confirmed hits were tested for their ability to induce the cell envelope stress responsive promoter piniBAC controlling expression of red fluorescent protein in an M. bovis BCG reporter strain. Using a fluorescence readout, the acetamide E11 was identified. Resistant mutant selection and whole genome sequencing revealed the mycolic acid transporter Mmpl3 as a candidate target of E11. Biochemical analysis using mycobacterial spheroplasts and various membrane assays suggest that E11 indirectly inhibits MmpL3-facilitated translocation of trehalose monomycolates by proton motive force disruption. E11 showed potent bactericidal activity against growing and non-growing M. tuberculosis, low cytotoxic and hemolytic activity and a dynamic structure activity relationship. In addition to activity against M. tuberculosis, E11 was active against the non-tuberculous mycobacterium M. abscessus, an emerging opportunistic pathogen. In conclusion, we identified a novel bactericidal anti-mycobacterial lead compound targeting MmpL3 providing an attractive starting point for optimization.